Pelatihan Manajemen Keuangan Internal dan Utang Kepada Karyawan Pt. Anak Rantau Riau - Jessica Novia; Candy Candy (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Good financial management has a very important role in the long-term success of a company. However, currently, there are still many companies that experience problems in terms of managing their company's finances, one of which is PT. Anak Rantau Riau. This company is a service and goods company engaged in sports, namely fitness and workout sports. PT. Anak Rantau Riau experienced problems in the form of differences between the money received in the company account and the revenue recorded in the point on-sales system and several times made payments twice for the same invoice. Seeing this, of course, there needs to be steps to follow up so that nothing like that happens in the future. To follow up on this, discussions with company employees were held to determine what platforms and techniques were suitable and easy to implement to overcome the company's problems. Then, followed by providing direction to employees regarding the utilization of Microsoft Excel and spreadsheets as well as knowledge about the importance of even the smallest difference in money in finance. Finally, there will be an assessment of the results of the training. The result of the follow-up is that the problem of discrepancies between the money in the account and the revenue recorded in the point on-sales system can be minimized and there is no need to pay invoices twice for one invoice. Keywords: Internal Financial Management, Debt Management, Point on Sales System